DETERMINANTS OF PREECLAMPSIA AMONG PREGNANT WOMEN IN INDONESIA: A CROSS-SECTIONAL STUDY - Umairo, Gusrida; Solehah, Ipah; Komariah, Euis; Rahmah, Irma Fauziah (Himpunan Perawat Medikal Bedah Indonesia (HIPMEBI) Regional Jawa Barat, 2025)
This study aims to identify the factors associated with the incidence of preeclampsia among pregnant women in Indonesia in 2023. A quantitative study was conducted using a cross-sectional design in April 2023. A total of 391 pregnant women participated in this study, selected through appropriate inclusion criteria. Data on relevant variables were collected through medical record observations. The variables examined included parity, maternal age, history of hypertension, history of obesity, and education level. Statistical analysis was performed using the Chi-Square test via SPSS to explore the relationship between each independent variable and the incidence of preeclampsia. Of the five variables assessed, four were found to be significantly associated with the occurrence of preeclampsia. These were parity (p = 0.000), maternal age (p = 0.000), history of hypertension (p = 0.000), and history of obesity (p = 0.001). These findings suggest that women with higher parity, advanced maternal age, a previous history of hypertension, or obesity are at increased risk of developing preeclampsia. On the other hand, education level was not found to have a statistically significant association with the incidence of preeclampsia (p = 0.144). The study concludes that parity, maternal age, history of hypertension, and obesity are significant predictors of preeclampsia among Indonesian pregnant women. Educational attainment, however, does not appear to play a significant role. These findings may inform targeted interventions and risk assessment strategies in maternal healthcare settings.Keywords: Preeclampsia, Education, Parity, Maternal Age, History of Hypertension, History of Obesity